The Effect of Knowledge Sharing, Talent Management, and Competence on Innovative Behavior and Performance in Textile Industry - Istikomah; Juli Riauwati; Eviana Widiati; Kartiwi (Jurnal Ilmiah Manajemen Kesatuan, 2026)
In a competitive industrial environment, textile companies are required to improve employee performance through effective management of human resources. This study aims to examine the influence of knowledge sharing, talent management, and employee competence on innovative behavior and employee performance in the textile industry of West Java, Indonesia. A quantitative approach was employed using a survey method, with data collected from 470 employees selected through proportionate cluster sampling. The data were analyzed using Structural Equation Modeling with LISREL 8.80. The results reveal that knowledge sharing, talent management, and employee competence have a positive and significant effect on innovative behavior, explaining 74.59% of its variance. Among these variables, employee competence shows the strongest contribution to innovative behavior. Furthermore, innovative behavior has a strong and significant influence on employee performance. These findings confirm that employee performance can be optimally enhanced when organizations foster innovative behavior supported by strong employee competence, effective knowledge sharing, and strategic talent management. Therefore, strengthening innovative behavior is a critical mechanism for translating human resource capabilities into sustainable performance improvements in the textile industry.